Establishing linkages between religiosity and spirituality on employee performance - Osman-Gani, Aahad M.; Hashim, Junaidah; Yusof, Ismail (Emerald Publishing, 2013)
Purpose – This paper aims to examine the impact of religiosity and spirituality on employee performance in multi-cultural and multi-religious organisations. Design/methodology/approach – This study adopted Religiosity Personality Index (MRPI) by Azimi et al., Spirituality Involvement and Beliefs Scale (SIBS) by Hatch et al., and Performance Measures by Sarmiento et al. The performance data was collected from employees, peers, and supervisors. The study administered and received all the 435 completed sets of questionnaires (435 employees, 870 peers, and 435 supervisors). Findings – SEM analysis showed that religiosity and spirituality have a significant positive relationship with employees’ performance. Better spiritual condition improves performance. Religion functions as a moderating variable in employees’ job performance. Research limitations/implications – This study has extended the knowledge of spirituality in the workplace by confirming that spirituality is more significant than religiosity in influencing employees’ performance. Religion, however, moderates spirituality-performance relationship. Practical implications – Based on the empirical findings of this study, organizations may formulate new policies and strategies for improving employee performance by allowing and encouraging spiritual activities in the workplace irrespective of religious and spiritual beliefs, thereby facilitating understanding and mutual respect. A culture of respect for diversity of beliefs and faiths should be cultivated in the workplace by enforcing appropriate codes of conduct as well as instilling values of tolerance, respect and compassion, which would result in more productive teamwork and improved performance. Originality/value – This is the only study that measured the impact of religiosity and spirituality on employees’ performance using three different sources of data: employees, peers, and supervisors.